Unlocking the Contradictory Outcomes of Presenteeism Through a Temporal Model: Effort Exertion as a Mediator - Chou, Chun-Yi; Mach, Merce (Frontiers in Psychology, 2021)
The effects of presenteeism, that is, attending work while sick or exhausted, are unclear as previous research has yielded contradictory results. The aim of this study is thus twofold: investigate the differential effects of short versus long-term presenteeism and corroborate the mediating effect of effort exertion on the relationship between presenteeism and work-related outcomes. We adopted a three-wave panel design and measured all the variables at three different points (initially, after one week and after one year) to understand the effects of presenteeism over time. Our sample consisted of 361 Chinese employees working in diverse industries in Taiwan. We analyzed the panel data using structural equation modeling and bootstrapping. Our results revealed that presenteeism was positively associated with increased effort, work engagement, and job performance after one week. By contrast, presenteeism after one-year was negatively associated with job performance and work engagement though positively associated with emotional exhaustion. Our research contributes to clarify paradoxical results regarding presenteeism’s consequences, as well as corroborating that effort exertion mediates the relationship between presenteeism and work outcomes. We also identify practical implications for organizations managing employees who work remotely, a more common reality with the outbreak of the COVID-19 pandemic, the ensuing lockdowns, and digitalization, which has started to become the norm for a significant proportion of working sectors. Finally, we suggest recommendations for future research on presenteeism.